Copper catalyzed access to functionalized oxazoles from oximes via carbenoids. Issue 23 (6th June 2018) - Nagaraju, Anugula; Sandeep, K.; Kumara Swamy, K.C.
Graphical abstract: Highlights: Functionalized oxazoles are prepared using copper catalysis. Oximes and carbenoid precursors have been utilized. Two reducible functionalities (esters or ester + cyano) are introduced on oxazoles. Abstract: An operationally simple, economical and straightforward synthesis of diverse oxazoles from oximes possessing a vicinal carbonyl group has been achieved by treatment of the latter with terminal diazo compounds like ethyl/benzyl diazoacetate and diazoacetophenone (which act as carbenoids) in one pot. At least two reducible functional groups (two ester groups or cyano + ester) are simultaneously introduced in one step. This reaction involves expulsion of a molecule each of N2 and water only as byproducts under copper catalysis. The structure of one of these oxazoles is confirmed by X-ray crystallography. Both the ester groups in the oxazole product could be reduced to alcohol moieties by using NaBH4 /EtOH.